Analisis Performance Centrifugal Pump dengan Mengunakan Computating Fluid Dinamyc (CFD) untuk Transfer Condensate di Area Onshore Processing Facilities Balongan PHE ONWJ - Mudjijanto Mudjijanto (SIMETRIS, 2021)
Condensate transfer is one part of upstream oil and gas production operations. Condensate is a liquid hydrocarbon obtained from gas wells. Transfer is carried out using a transfer pump. In the activity of using the pump, we need to analyze the pump parameters. The aim is to evaluate the energy performance of the pump according to the variation of the velocity of the fluid being flowed and to determine the pump's working point. The research was conducted by testing the performance of the pump in the field and analyzing it using CFD in solidwork application. The method applied is to change the flow variation with a fluid velocity of 5.9m/s; 17.2m/s ; 20.5m/s. Tests are carried out to determine the pressure and temperature of the pump. The test data in the field will then be compared with the simulation data in the application. The results of the analysis carried out using a flow variation of 5.9 m/s and 17.2 m/s obtained a pressure and temperature comparison between the actual and the simulated according to the operating conditions of the pump. In the analysis with a speed variation of 20.5 m/s there is an indication of a decrease in pump pressure under actual conditions in the field, namely 39 Psi, while in the simulation with ideal conditions it exceeds the operating pressure of the pump. So the conclusion obtained is that the variation in flow causes differences in pump performance in terms of Pressure and Temperature. At a variable speed of 20.5 m/s there is a change in pump performance and if left unchecked can cause damage in the long term.